Πέτρινη τοξωτή γέφυρα νοτιότερα των πηγών του ποταμού Αγγίτη, κοντά στην κοινότητα Πηγών - Σ. Καζαντζίδης (1993)
Πέτρινη τοξωτή γέφυρα νοτιότερα των πηγών του ποταμού Αγγίτη, κοντά στην κοινότητα Πηγών